Sa-OR-S120-2 - The Indirect Effect Of Distributive Justice On Turnover Intention Through Cyberbullying Practices And The Role Of People Orientation Leadership - Costa Ferreira, P.A. N.; Ferreira, A.I.; Veiga Simão, A.M. (EAWOP 2017, 2017)
Cyberbullying has increasingly become an occurrence in organizations, however, this phenomenon remains understudied. To understand the mediator role of cyberbullying and the organizational factors that affect turnover intention, the present study examined the mediating and moderating variables in the relationship between distributive justice and turnover intention using a sample of 273 employees from 33 different companies. Hierarchical Linear Models revealed that distributive justice is related to turnover intention and that the perceived departmental practices of cyberbullying mediated this relationship. We also found that at the supervisory-level of analysis, a leadership with lower orientation towards people moderated the indirect relationship between organizational justice and turnover intention. The current study has important implications for the study of cyberbullying in organizational contexts and its effect in the indirect relationship between perceptions of distributive justice and negative organizational outcomes (turnover). Moreover, our study emphasizes the role of leadership practices reinforcing that departments with leaders with lower orientation towards people tend to promote a higher indirect effect in the relationship between distributive justice and turnover intention.